Vpliv razvoja opreme na učenje in varnost pri kajtanju - Kolbezen, Anže (Šport (Ljubljana), 2018)
Kiteboarding is an adrenaline sport with improving safety considerations. Sport is popular across different age groups. Development of the gear has increased safety during sport engagement and decreased injury rate. However, research regarding kiteboarding still remains scarce. The aim of this study was to examine the improvement of teaching methodology and gear on safety during kiteboarding. A total of 100 participants were included into the study. Our results demonstrated that development of gear and teaching methodology improved safety during kiteboarding, although the duration of kiteboarding lessons did not decrease. The latter is associated with upgraded teaching methodology and less self-taught kiters. Furthermore, we demonstrated that sport related accidents occur due to human errors and not because of safety gear malfunctions. Our results provide a novel insight into development of kiteboarding safety and demonstrate its significance during learning process in order to reduce injury prevalence before and during engagement in this popular water sport.
Keywords: kajtanje; metodika; razvoj opreme; učenje; varnost; vodni športi